Peran Teman Sebaya Dalam Penanaman Pendidikan Karakter Pada Masa Pandemi Di SDN Andong Boyolali - Wachid Pratomo; Nadziroh Nadziroh; Chairiyah Chairiyah (STAHN Mpu Kuturan Singaraja, 2021)
This research is aims to describe the the role of peers in inculcating character education during pandemic in SDN Andong Boyolali. The method used in this research is descriptive qualitative. The data analysis technique used in this study was an interactive model from Miles and Huberman which consisted of several stages, namely data collection, data reduction, data presentation, and conclusion drawing. The data result show that: Peers provide a role for inculcating character education as an example of behavior, give support, and teaches social skills acquired in learning. Constraints for the role of peers in planting character education that is students who hang out with friend bad character, lack of facilities that support character cultivation, lack of communication between teachers and parents, and lacking lees in depht learning in the cultivation of character education. While factors that influence its success that is school environmental factors, family and society Efforts to overcome obstacles the role of peers in planting character education that is provide a persuasive approach, provide adequate facilities, increase cooperation between teachers and parents, provide knowledge and socialization about character education, and direct students to behave well